Learning Experiences in Higher and Further Education- An Innovative Socialentrepreneurship Project in a Public Mexican University - Betancourt, Ignacio Ortiz; María del Carmen Meza Téllez; Leidy Margarita López Castro; Jorge Samuel Berdón Carrasco (European Journal of Social Science Education and Research, 2019)
This innovative educational project is the result of the work of a group of academics, who met the challenges of the 21st century, added their specific visions and made contact with transdisciplinarity and the formation of a significant formation in their students of the Educational Administration Program with learning orientated to the transfer, that is to say new fields of application (Campirán et al, 2005); this transit was possible through the metacognition resulting from the synergy found at the Universidad Veracruzana (Mexico) and the HEC University Montreal (Canada) to generate spaces that transcend the classrooms and thus express this vision that would allow to refocus and redirect their educational goals (Campirán et al, 2005). Internationalization of social entrepreneurship is part of an educational bonding project led by the academic group CA-UV-367 “Entrepreneurship, Management and Internalization” from which academics articulate formally the critical and complex exercise for an object-relation of learning of different visions: academic formation (curricular design); accommodation (spiral organization); development of visions based on competencies (Campirán, 1999, in Morado, 1999) and integrative concepts (Campirán et al, 2005). The results obtained from the exercise and the use of the transdisciplinary vision approach greatly enriched the units of competence and the curricular contents of educational experiences: Strategic and economic planning over time promoted and strengthened in students their comprehensive and flexible training in addition to enhancing their resources and academic capabilities by projecting themselves as members of a global community.
Keywords: innovativeeducational project; social entrepreneurship; educational bonding.